Experimental and numerical analysis of strengthening prestressed concrete cylinder pipes using a post-tensioning method - Zhao, Lijun; Dou, Tiesheng; Li, Chunlei; Li, Meng (Frontiers in Earth Science, 2023)
Prestress loss caused by broken wires can lead to a decline in the carrying capacity of prestressed concrete cylinder pipes (PCCPs). The strengthening of PCCPs using a post-tensioning method is becoming more and more widely utilized to restore strengthened pipes to the needed design capacity and to withstand combined loads. There is no need to drain the pipe during strengthening construction, and this strengthening actively replenishes the prestress loss caused by wire breakage at a cost-effective price. To verify the strengthening effect of this method, a full-scale test and its corresponding three-dimensional finite-element model were established. A three-dimensional numerical model of three continuous prototype pipes was established and accounted for the particularity of the bell and spigot. The numerical model of prestressing wires was optimized in two aspects, which was more in line with the actual situation. The spiral winding method instead of single winding was adopted to apply prestress, and the prestressing wires with a broken point were partitioned into two separate areas due to the bond quality between the mortar coating and the wires. The simulation and the full-scale test both contain the five processes of strengthening with external prestressed strands as follows: pressurized to working pressure→breaking the prestressing wires until visible cracks propagate→gradual depressurization to artesian pressure→the tensioning operation of strands→and pressurized to design pressure. A sensitivity analysis of the related factors of strengthening was performed through finite-element simulation to provide a better understanding of the design. The simulation results were consistent with the data on the full-scale test and indicated the rationality of this process. The strengthening of PCCP with a post-tensioning method can meet the design demand and is a feasible strengthening method. The working pressure and control coefficient of tensioning have the most significant impact on the strengthening effect. Technical recommendations and a better understanding of the application of the post-tensioning method on PCCP are provided in this study.